SOCRATES’ DIALECTICAL METHOD - Fedoryshyn , Dmytro; Shtanko , Valentyna (Collection of scientific papers «ΛΌГOΣ», 2022)
Socrates – a great ancient Greek philosopher – believed that every man is capable of having their own point of view, but at the same time he was convinced, that this fact doesn’t mean that everyone has their own truth. In order to substantiate his views, Socrates used the method developed by him, which went down in the history of philosophy as Socratic method, to be exact, dialectical method, the art of dialectical dispute [1]. Dialectics is a method by which ethical concepts are presented and developed, substantiated. For Socrates, philosophy means the consideration of a specific moral phenomenon, in the process of which we come to the definition of what is this phenomenon, that is, to determine its essence. Socrates believed that cognition is primarily self-knowledge, but before moving on to this, we must recognize that "I know that I know nothing."